Defaunation of tropical forests reduces habitat quality for seed‐dispersing bats in Western Amazonia: an unexpected connection via mineral licks. (21st May 2013) - Ghanem, S. J.; Voigt, C. C.
Abstract Hunting reduces the overall abundance of larger mammals in many tropical forests with often direct negative consequences such as reduced seed dispersal. In Western Amazonia, legal and illegal hunting practices have a substantial negative impact on populations of larger mammals. Yet, large mammals are important for maintaining so‐called mineral licks; nutrient‐rich muddy depressions that are also used by smaller mammals such as bats for geophagy. Mineral licks seem to play a particularly important role during the reproduction of frugivorous bats because pregnant and lactating bats supplement their nutrient‐poor diet with muddy water from mineral licks. In our study, we asked first if mineral licks deteriorate when not maintained by large mammals. Second, we tested if mineral lick deterioration reduces the visitation rate of frugivorous bats. For mineral licks in areas with intensive hunting, we expected to find signs of deterioration such as increased plant coverage. In addition, we expected to capture fewer bats at deteriorated licks than at natural licks. Indeed, mineral licks in forests with intensive hunting were covered by more seedlings and leaf litter than licks in pristine forests. Also, we encountered fewer bats at deteriorated mineral licks than at natural licks. We conclude that defaunation of Amazon forests affects not only large mammals directly but most likely also fruit‐eating bats because reproducing female bats may be limited in their ability to access nutrient‐rich soils of mineral licks. Thus, hunting puts the ecosystem services of seed‐dispersing mammals at risk in two ways, by eliminating large mammals and by reducing habitat quality for fruit‐eating bats.